PRINSIP KEADILAN SOSIAL DALAM SISTEM TENURIAL DI WILAYAH PESISIR DAN PULAU-PULAU KECIL DI INDONESIA - Farida Patittingi (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
Social justice as a principe of Pancasila should become a basis of political law on a regulating the national agrarianresources, especially at coastal areas and small islands. This is to realize the welfare of all the Indonesian citizens. Theinternalization principle of social justice in regulating land tenure tand ownership at the above mentioned places can show thebalannced and propotioronal distribution of land tenure and ownership for stakeholders; ivestors, society and the government.Keywords: Citizen, investor, and goverment.